2013
DOI: 10.1590/s1517-83822013000300050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of open drainage ditch design on bacterial and fungal communities of cold waterlogged paddy soils

Abstract: A field experiment established in 1980 was conducted to evaluate the effects of open drainage ditch applied for water removal on bacterial and fungal communities of cold waterlogged paddy soils in 2011. In this experiment, traditional plate counting and temperature gradient gel electrophoresis were employed to characterize the abundance and diversity of soil bacterial and fungal communities. Four different distances from the open drainage ditch, 5, 15, 25 and 75 m with different degrees of drainage were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous studies showed shifts in the soil bacterial and fungal communities with distance gradient from the ditch [9,51]. For example, Qiu et al [52] revealed that fungal diversity was higher at a plot 5 m from the ditch related to the well-drained soil condition and the improvements in nutrient availability compared to the plot at a 75 m distance with poor drainage condition. Therefore, changes in fungal community structures in peat soil might serve as a sensitive indicator for changes in soil properties.…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchmentioning
confidence: 99%
“…Previous studies showed shifts in the soil bacterial and fungal communities with distance gradient from the ditch [9,51]. For example, Qiu et al [52] revealed that fungal diversity was higher at a plot 5 m from the ditch related to the well-drained soil condition and the improvements in nutrient availability compared to the plot at a 75 m distance with poor drainage condition. Therefore, changes in fungal community structures in peat soil might serve as a sensitive indicator for changes in soil properties.…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchmentioning
confidence: 99%
“…Such concentrations were toxic to the mutant yap1Δ strain while had no effect on the wild type yeast strain. [24]. Some foods rich in polyphenols have been shown to maintain normal cell growth even when cells are stressed with H 2 O 2 or menadione [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…PGPR application which contains phosphate solubilizing bacteria supposed to be has a minor effect on soil microbes. Interestingly, Bio IPM had no significant effect on the phosphate solubilizing bacteria in wet season, presumably because high waterlogging would adversely affect the life of soil bacteria (Qiu et al 2013). Finally, it can be stated that Bio IPM improves soil microbiology by increasing total soil bacteria and phosphate solubilizing bacteria.…”
Section: Discussionmentioning
confidence: 99%